Bibliometric Analysis of Management Approaches in Optimizing Athlete Potential in Badminton - Sumantri, Ajis; Ertanto, Dody (Indonesian Journal of Sport Management, 2024)
This study aims to determine the contribution of arm muscle strength to serving This research aims to conduct a bibliometric analysis of management approaches to optimize the potential of athletes in badminton. Through searching and selecting articles from various trusted sources, we analyze research trends, main focuses, and developments in management approaches to improve the performance of badminton athletes. The results of the analysis show that there has been increasing research interest in this topic over the past several decades, focusing on team development strategies, time management, mental training, and the use of technology in coaching athletes. In addition, identifying key concepts such as leadership, motivation, and competitive strategy is also a major highlight in the literature. The practical implications of these findings include the importance of implementing a holistic and sustainable management approach to optimize the potential of badminton athletes. This study provides valuable insights for sports practitioners, coaches and researchers to continue developing effective strategies for advancing athlete performance in badminton.